Serotonin reuptake inhibitors in Obsessive-Compulsive Disorder: antidepressant or antiobsessional agents? - Giuseppe Maina; Enrico Pessina; Andrea Aguglia; Filippo Bogetto (Clinical Management Issues, 2009)
The recommended pharmacological agents for the treatment of Obsessive-Compulsive Disorder (OCD) are serotonin reuptake inhibitors (SRI), used also as antidepressant drugs. Nevertheless, the therapeutic profile of SRIs shows a lot of differences in OCD and in depression, as demonstrated in the trials here described. From a pharmacological point of view, antidepressant effect can be obtained with every monoamine reuptake inhibitor, whereas a predominant serotonin reuptake inhibition is required to result in an antiobsessive effect; moreover, adding pindolol to SSRI therapy, generate opposite effects on SSRI response latency. From a clinical point of view, the trials have highlighted differences in the following fields: response rate, therapeutic dose, response latency, response curve. Taken together, these findings suggest that SRIs have two different clinical properties, antiobsessional effect and antidepressant effect, that could be due to different mechanisms of actions: further studies have to be performed the better to understand the pathophysiology of OCD.